Spillovers between Twitter uncertainty indexes and sector indexes: evidence from the US - El Khoury, Rim (2022)
The study examines the spillover between Twitter Uncertainty Indexes (TUI) and 10 US sectors. Our methodology is twofold: a time-varying parameter vector autoregression (TVP-VAR) to explore the dynamic connectedness among sectoral returns and a regression, mainly ordinary least squares (OLS) and quantile, to explore the role of TUI in explaining the total connectedness and the net connectedness of each sector. First, our results indicate that industrials and materials are the main net transmitters of shocks, and utilities and energy are the main recipients. Second, TUI increases total connectedness only at higher values of connectedness, suggesting that more diversification benefits are available at low levels of connectedness and TUI. Third, the direction of the TUI's effect on net connectedness changes from one sector to another, indicating that TUI can signal either good or bad news, depending on the sector.